Morbilidad cardiovascular trans y postoperatoria en pacientes geriátricos. Hospital Provincial General Docente Riobamba, 2016–2019 - Santillán Castillo, Violeta Sofía (2020)
As we age the body's response is different on many ways, so comprehensive and individualized care for the elderly is a priority, especially in patients who have had surgery. The objective of this research was to determine the trans and postoperative cardiovascular morbidity in geriatric patients operated at the Riobamba Provincial General Teaching Hospital. For this, basic, non-experimental research was carried out with a descriptive, correlational, explanatory, retrospective and mixed scope approach. The population consisted of all 257 elderly patients who underwent surgery during the study period. The sample was made up of 207 older adults. The main results include a predominance of patients between 65 and 70 years old (57.00%), male (52.67%) and with associated comorbidities (81.64%). High blood pressure (86.98%) and diabetes mellitus (24.85%) were the most identified. 54.11% of patients underwent emergency surgery, with the predominant duration of surgeries greater than two hours (72.95%) and using general anesthesia (93.24%). 72.95% of the elderly had cardiovascular complications. 78.15% in the post-surgery period and 21.85% in the trans-surgery period. Tachycardia (47.72%), hypertension (37.09%) and hypotension (23.18%) were the most representative. It concludes that the incidence of cardiovascular complications during the trans and post-surgery period in older adults is high; however, there were no deaths from causes related to the surgical process or the presence of complications during it.